Ambilan oksigen maksimal (V02,â) pada usia lanjut: Hubungan antara Lama dan Frekuensi Latihan dengan Tinggi VO2rna,= Maximum Oxygen Uptake (VO) : Relation betweenDuration and Frequency ofnercise to VO2max - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
,Twenty eight elders (age range 55-77 years) who were active exercise in "Klub Jantung Sehat" Yogyakarta were cross sectionally studied. The aim of this study was to know the difference of ITC),, between person who performed exercise more and less than 10 years. Also the relations between duration, and frequency of exercise to 1/0.. Questionnaire was used to divide subjects into three groups which were based on period, duration and frequency of exercises prior to this study were done. Indirect measurement of VO2, was done by using Monark Ergocycle according to Astrand's method. Blood pressure and rest-heart rate were recorded before the exercise test. Heart rate and blood pressure during the test were also recorded every 1 and 5 minutes, respectively. Recovery-heart rate immediately was recorded after completing this test. The results were no significant differences between ITOx's person who performed exercise more and less than 10 years, no relations between duration and VOA,,. However, relation was significant between frequency of exercise and V02â,.. Conclusion: The results indicate that to maintain the level of VOâ in elders, they should exercise regularly.